One‐Step Interfacial Functionalization and Synthesis of Mo–Modified TiO2 Nanocrystalline as Composite PtRu Anode Catalyst Support for DMFCs. Issue 17 (2nd May 2019) - Li, Jia‐Long; Zhao, Lei; Li, Xi‐Fei; Hao, Su‐E; Wang, Zhen‐Bo
Abstract: A one‐step approach of synthesis and interfacial functionalization of Mo to modify TiO2 nanocrystallines (iMTNCs) derived from tetrabutyl orthotitanate is proposed through mild alkaline and reductive hydrothermal reaction. Ultrafine crystallite sized TiO2 nanocrystallines (TNCs) with functionalized interface are obtained from the interfered synthesis process by hydrothermal etching and liquid phase infiltration of Mo dopants. The composite iMTNCs−C (incorporated with carbon black) is employed as the functionalized support for PtRu binary catalyst towards methanol electrooxidation. The resultant PtRu/iMTNCs−C catalyst manifests 1.68 times higher mass activity comparing to that of the un‐functionalized catalyst (PtRu/TNCs−C) and 1.44 times enhanced mass activity to PtRu/C catalyst with improved durability. These improvements in catalytic performance are attributed to the electronic donation from Mo functionalized interface of iMTNCs to PtRu nanoparticles (NPs) and ultrafine crystallite sized architecture of composite support. This work suggests a potential application of the functionalized nanocrystalline support material in fuel cell. Abstract : Ultrafine TiO2 nanocrystallines with Mo functionalized interface were synthesized via one step hydrothermal reaction as high performance PtRu catalyst support with improved electron donation effects. The resultant PtRu/iMTNCs−C catalyst manifests 1.68 times higher mass activity comparing to that of the un‐functionalized catalyst (PtRu/TNCs−C) and 1.44 times enhanced mass activity to PtRu/C catalyst with improved durability. This work suggests a potential application of the functionalized nanocrystalline support material in fuel cell.